PENYULUHAN INTERNET SEHAT SEBAGAI EDUKASI DAN INFORMASI BAGI ANGGOTA FATAYAT NU KECAMATAN CILEDUG TANGERANG - Devy Putri Kussanti; Fifit Fitriansyah; Susilowati; Parlin Harbet (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
The increasingly advanced digitalization in Indonesia has led to the rise of crime in cyberspace. This can be anticipated by providing education about how to surf the internet in a healthy and good way in cyberspace. The intensity of internet use is increasing during the covid-19 pandemic and this is then accompanied by an increase in internet use that is not good when surfing the internet. This was then used as an anticipatory measure by Fatayat, Ciledug District, Tangerang in order to avoid healthy internet violations. In addition, many of the community service participants still lack information and understanding about healthy internet. The existence of community service this time with the counseling method on healthy internet is expected to provide additional references regarding surfing in cyberspace properly and ethically and also increase the vigilance of Fatayat members, Ciledug District, Tangerang in the current digitalization era. Extension activities are carried out using a virtual communication method via zoom, this is to minimize crowds and new clusters of covid-19, especially during the omnicorn type of covid.